Wnt inhibition enhances browning of mouse primary white adipocytes. (2nd April 2016) - Lo, Kinyui Alice; Ng, Pei Yi; Kabiri, Zahra; Virshup, David; Sun, Lei
ABSTRACT: The global epidemic in obesity and metabolic syndrome requires novel approaches to tackle. White adipose tissue, traditionally seen as a passive energy-storage organ, can be induced to take on certain characteristics of brown fat in a process called browning. The "browned" white adipose tissue, or beige fat, is a potential anti-obesity target. Various signaling pathways can enhance browning. Wnt is a key regulator of adipocyte biology, but its role in browning has not been explored. In this study, we found that in primary mouse adipocytes derived from the inguinal depot, Wnt inhibition by both chemical and genetic methods significantly enhanced browning. The effect of Wnt inhibition on browning most likely targets the beige precursor cells in selected adipose depots.